OP006 Apremilast for active ulcerative colitis: a phase 2, randomised, double-blind, placebo-controlled induction study. (16th January 2018) - Danese, S; Neurath, M; Kopon, A; Zakko, S; Simmons, T; Fogel, R; Maccarone, J; Zhan, X; Usiskin, K; Chitkara, D
Abstract: Background: Apremilast is an oral small-molecule inhibitor of phosphodiesterase 4 that works intracellularly to modulate a wide array of pro- and anti-inflammatory mediators in ulcerative colitis (UC). Methods: Patients with active UC (defined as a total Mayo score [TMS] of ≥6 to ≤11, with a Mayo endoscopic score [MES] of ≥2) who failed at least one conventional therapy for UC and were naïve to biologic therapy were randomised in a 1:1:1 ratio to receive apremilast 30 mg BID (APR30), apremilast 40 mg BID (APR40), or placebo (PBO) for up to 12 weeks. The primary endpoint of the study was TMS clinical remission at Week 12. Endoscopy was read centrally by independent experts blinded to treatment allocation and time point. Results: A total of 170 patients were randomised to PBO ( n = 58), APR30 ( n = 57), or APR40 ( n = 55). There were no differences in baseline disease characteristics, and mean baseline TMS and MES were 8.3 and 2.6, respectively. A significantly higher proportion of patients treated with APR30 achieved TMS clinical remission (Δ18%) and modified Mayo score (MMS) clinical remission (Δ25%) compared with PBO. A higher proportion of patients treated with APR30 and APR40 achieved a clinical response at Week 12 compared with PBO, but the result was only significant for the APR40 treatment group. At Week 12, a significantly higher proportion of patients treated with APR30 achieved a decrease of at least one point from baseline MES (Δ32%) and an MES ≤1 (Δ32%) compared with PBO. Both APR30 and APR40 treatment groups showed a trend for a higher proportion of patients achieving histological remission, defined as a Geboes score <2, compared with the PBO group. A significantly higher proportion of patients treated with APR30 achieved mucosal healing (MES ≤1 with Geboes score <2) (Δ18%) compared with PBO. Patients treated with APR30 achieved significant improvements in percent changes from baseline in hsCRP at Weeks 4, 8, and 12 and faecal calprotectin at Weeks 2, 4, and 8 compared with PBO. A similar safety profile was seen in patients treated with APR30 and APR40. Conclusions: In this 12-week, phase 2 study, patients with active UC treated with APR30 had clinically meaningful improvements in symptoms, endoscopy, biomarkers, and mucosal healing compared with PBO. The observed adverse events were consistent with those expected in UC patients and were also consistent with the known safety profile of apremilast.